User Generated Content di Media Sosial Sebagai Strategi Promosi Bisnis - Faizal Wayan Umbara (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
Social media has a tremendous impact on the way people interact and exchange information. Social media provides a place for anyone to express themselves, showing likes or dislikes about a product in front of an audience of social media users. Content that contains brand reviews made by consumers themselves without any sponsors is included in the user generated content (UGC) category. This study wants to find out how user generated content on social media becomes a business promotion strategy. This is related because User generated content is part of electronic word-of-mouth (eWOM), where there is an exchange of information that can influence potential buyer's decisions. This study uses a qualitative approach by conducting a literature review. The results of this literature review show that user generated content on social media that reviews a brand or product can influence the interests of others. So, brand owners or producers need to make efforts to maintain relationships with consumers and with users of user generated content in order to increase brand promotion through digital marketing.